Annexation, normalization and the two-state solution in Israel-Palestine - Shemer-Kunz, Yoav (Frontiers in Political Science, 2023)
Israel's annexation policies of the West Bank is undermining the two-state solution, entrenching a one-state reality of unequal rights from the Mediterranean sea to the Jordan river. Taking into account this one-state reality, in which two national groups live in one mixed territory, this study explores how Israelis and Palestinians perceive the conflict today and its future solution. Based on 38 in-depth interviews with both Israeli and Palestinian political leaders, the study finds that despite the one-state reality on the ground, the Palestinians still insist the two-state solution is still the best way to end Israel's occupation since 1967, as this solution has a wide International support since a few decades. The Palestinians are still attached to the national project of statehood as a tool of liberation from the occupation. In fact, the Palestinians see any attempt to reconsider this solution as taking a risk of normalization of the current situation of one-state reality. Similarly, pro-Palestinian Israelis also still refer to the two-state solution, even though they do not believe it is still possible, but rather as a slogan to show that some solution is necessary, against the normalization of the apartheid. However, the main Israeli vision is not a territorial partition of the Land of Israel but shrinking the conflict, offering the Palestinians economic peace and 'normal life', but without political collective rights such as the right to self-determination. While the Israelis suggest that Palestinians will end up accepting this deal and give up their national aspirations, Palestinians insist this is a fantasy and wishful thinking, Finally, the study explores the current debate on alternative solutions which are not based on partition of the land from the river to the sea, arguing that an alternative one-state option is bi-national in nature. The article suggests that future research should focus on Palestinians in Israel, who were not part of the national project of independent statehood and rather developed their own vision of living together with Jewish Israelis, based on partnership and equal rights rather than partition and separation.